2018
DOI: 10.1159/000493297
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma Lucidum Polysaccharide Peptide Alleviates Hepatoteatosis via Modulating Bile Acid Metabolism Dependent on FXR-SHP/FGF

Abstract: Background/Aims: Non-alcoholic fatty liver disease (NAFLD) encompasses a series of pathologic changes ranging from steatosis to steatohepatitis, which may progress to cirrhosis and hepatocellular carcinoma. The purpose of this study was to determine whether ganoderma lucidum polysaccharide peptide (GLPP) has therapeutic effect on NAFLD. Methods: Ob/ ob mouse model and ApoC3 transgenic mouse model were used for exploring the effect of GLPP on NAFLD. Key metabolic pathways and enzymes were identified by metabolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 58 publications
(63 reference statements)
0
37
0
Order By: Relevance
“…18) Zhong et al reported that the Ganoderma lucidum polysaccharide peptide (GLPP) can alleviate hepatoteatosis. 31) Our previous study demonstrated that FYGL had an antihyperlipidemic effect in addition to antidiabetic in vivo. 24) Our studies on the mechanism found that FYGL improved the p-AMPK level along with the p-ACC and CPT-1 expressions increased, inhibited the expressions of fat-synthesis-related proteins FASN and SREBP1, leading to the steatosis inhibition, which implied that FYGL inhibit the lipid synthesis through AMPK pathway.…”
Section: Discussionmentioning
confidence: 98%
“…18) Zhong et al reported that the Ganoderma lucidum polysaccharide peptide (GLPP) can alleviate hepatoteatosis. 31) Our previous study demonstrated that FYGL had an antihyperlipidemic effect in addition to antidiabetic in vivo. 24) Our studies on the mechanism found that FYGL improved the p-AMPK level along with the p-ACC and CPT-1 expressions increased, inhibited the expressions of fat-synthesis-related proteins FASN and SREBP1, leading to the steatosis inhibition, which implied that FYGL inhibit the lipid synthesis through AMPK pathway.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous bioactive constituents of G. lucidum , including terpenes, proteins, polysaccharides, amino acids, flavonoids, alkaloids, steroids, mannitol, and other compounds, have been revealed [ 12 ]. Pharmacological studies have determined that G. lucidum polysaccharides and triterpenes have multiple pharmacological activities [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to a previous study, the PA-induced HepG2 cell hepatosteatosis model is commonly used that identify bioactive compounds to inhibit lipid accumulation. For example, Zhong et al demonstrated that the Ganoderma lucidum polysaccharide peptide (GLPP) reduced the accumulation of lipid droplets and the content of TG in the hepatosteatosis model of HepG2 cells [46]. Huang et al reported the preventive and therapeutic effects of resveratrol on PA-induced hepatocyte steatosis in HepG2 cells [47].…”
Section: Discussionmentioning
confidence: 99%